2017
DOI: 10.1007/s00417-017-3705-y
|View full text |Cite
|
Sign up to set email alerts
|

The clinical outcomes of surgical management of anterior chamber migration of a dexamethasone implant (Ozurdex®)

Abstract: In our study, not all patients required surgical removal of the implants. Repositioning the implant back into the vitreous cavity may be considered as an option in cases involving the first episode with no significant corneal endothelial decompensation. Considering potential anterior segment complications and the loss of drug effectiveness together, an individualized approach is recommended to obtain the best treatment outcomes and to minimize the risk of corneal complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…In a retrospective review of 924 DEX implantations performed, Kang et al reported four cases of anterior chamber migration in the presence of a compromised posterior capsule, [10] as we observed. In another previous report, corneal oedema was observed when anterior migration occurred over 3 weeks after implant.…”
Section: Discussionsupporting
confidence: 75%
“…In a retrospective review of 924 DEX implantations performed, Kang et al reported four cases of anterior chamber migration in the presence of a compromised posterior capsule, [10] as we observed. In another previous report, corneal oedema was observed when anterior migration occurred over 3 weeks after implant.…”
Section: Discussionsupporting
confidence: 75%
“…Several previous publications mention the migration of a dexamethasone implant as an adverse effect of treatment with the Ozurdex implants, but most authors detail the techniques on how to push the implant back into the vitreous cavity by flipping it through the pupil or iridotomy [1,2]. This is, however, not without risks, since the probability of the dexamethasone implant migrating back into the anterior chamber is very high.…”
Section: Resultsmentioning
confidence: 99%
“…It remains in the vitreous cavity for up to 3 months during which it disintegrates, exuding a daily dose of drug until it completely dissolves. The treatment is very efficient, however, in very rare cases, the implant can migrate during these 3 months into the anterior chamber, either through the pupil in aphakia, through fragile lens zonules, or through an iridotomy [1]. Given the confined anatomical situation in the anterior chamber, the implant will mechanically irritate the corneal endothelium and corneal oedema and opacity will result [2].…”
Section: Management Of Anterior Chamber Dislocation Of a Dexamethasonmentioning
confidence: 99%
“…In addition, different risk factors for anterior chamber migration have described in a few reports. Some studies have reported that, in aphakic vitrectomized eyes, the implant can maneuver through a pupil, through an iridectomy, and around an IOL to enter the anterior chamber [8,10,15,16]. All of those cases had common histories of a vitrectomy and either weak zonules, a defect, or a missing posterior capsular membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the risk of cataract formation and steroid-induced glaucoma, migration of the dexamethasone implant into the anterior chamber is another possibly severe complication [6,7]. The anterior chamber dislocation of a dexamethasone implant has recently been described in a few reports [8][9][10][11][12]. When migration into the anterior chamber occurs, the patient is at risk for corneal endothelial damage and corneal edema or decompensation.…”
Section: Introductionmentioning
confidence: 99%